Language teacher associations in Japan: knowledge producers and/or knowledge disseminators. (30th March 2016) - Stewart, Alison; Miyahara, Masuko
Abstract: To investigate the role of language teacher associations (LTAs) vis-à-vis their members, the case of Japan is notable for the apparent disparateness among the more than 50 associations that have formed over the past 90 years. An historical overview reveals that LTAs in Japan have emerged in four distinct waves, and a survey of representative associations from each of these waves clarifies some current differences between the groups. As a theoretical framework in which to explore these differences, we draw on Foucault's concept of power/knowledge, which proposes a hierarchy between those who produce knowledge and those who disseminate or consume it. According to this scheme, the second- and third-wave LTAs are categorized as knowledge producers, while the first- and fourth-wave LTAs are categorized as disseminators of knowledge promoted by the state or marketed by commercial interests. We conclude by considering the implications of these LTA roles for teacher autonomy and professionalization.